Plasmacytoid Dendritic Cells as a New Therapeutic Target for Autoimmune Pancreatitis and IgG4-Related Disease - Minaga, Kosuke; Watanabe, Tomohiro; Hara, Akane; Yoshikawa, Tomoe; Kamata, Ken; Kudo, Masatoshi (Frontiers in Immunology, 2021)
Although plasmacytoid dendritic cells (pDCs) able to produce large amounts of type 1 interferons (IFN-I) play beneficial roles in host defense against viral infections, excessive activation of pDCs, followed by robust production of IFN-I, causes autoimmune disorders including systemic lupus erythematosus (SLE) and psoriasis. Autoimmune pancreatitis (AIP), which is recognized as a pancreatic manifestation of systemic immunoglobulin G4-related disease (IgG4-RD), is a chronic fibroinflammatory disorder driven by autoimmunity. IgG4-RD is a multi-organ autoimmune disorder characterized by elevated serum concentrations of IgG4 antibody and infiltration of IgG4-expressing plasmacytes in the affected organs. Although the immunopathogenesis of IgG4-RD and AIP has been poorly elucidated, recently, we found that activation of pDCs mediates the development of murine experimental AIP and human AIP/IgG4-RD via the production of IFN-I and interleukin-33 (IL-33). Depletion of pDCs or neutralization of signaling pathways mediated by IFN-I and IL-33 efficiently inhibited the development of experimental AIP. Furthermore, enhanced expression of IFN-I and IL-33 was observed in the pancreas and serum of human AIP/IgG4-RD. Thus, AIP and IgG4-RD share their immunopathogenesis with SLE and psoriasis because in all these conditions, IFN-I production by pDCs contributes to the pathogenesis. Because the enhanced production of IFN-I and IL-33 by pDCs promotes chronic inflammation and fibrosis characteristic for AIP and IgG4-RD, neutralization of IFN-I and IL-33 could be a new therapeutic option for these disorders. In this Mini Review, we discuss the pathogenic roles played by the pDC-IFN-I-IL-33 axis and the development of a new treatment targeting this axis in AIP and IgG4-RD.